2015
DOI: 10.1183/13993003.00319-2015
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnoea and the hypothalamic–pituitary–adrenal axis in men and women: effects of continuous positive airway pressure

Abstract: Previous findings on the association of obstructive sleep apnoea (OSA) and the hypothalamic-pituitary-adrenal (HPA) axis are inconsistent, partly due to the confounding effect of obesity and infrequent sampling. Our goal was to examine whether in a relatively nonobese population, OSA is associated with elevated cortisol levels and to assess the effects of a 2-month placebo-controlled continuous positive airway pressure (sham-CPAP) use.72 subjects (35 middle-aged males and post-menopausal females with OSA, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 33 publications
3
54
0
1
Order By: Relevance
“…Kritikou et al showed that OSA patients have higher 24-hr cortisol levels compared to controls, and the cortisol profile was reduced by CPAP [50]. Similarly, CPAP withdrawal increased nocturnal cortisol and was shown to increase dynamically with awakenings from sleep [24].…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…Kritikou et al showed that OSA patients have higher 24-hr cortisol levels compared to controls, and the cortisol profile was reduced by CPAP [50]. Similarly, CPAP withdrawal increased nocturnal cortisol and was shown to increase dynamically with awakenings from sleep [24].…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…However, it is not known whether aldosterone secretion decreases after the treatment of obstructive sleep apnea in women. Obstructive sleep apnea is related to the activation of the hypothalamic‐pituitary‐adrenal axis and increased cortisol levels, although these results vary between studies 28. Continuous positive airway pressure lowers the cortisol levels, but it is not known whether there are sex differences in this effect 28…”
Section: Discussionmentioning
confidence: 99%
“…More recently, CPAP has been shown to potentially have a protective role in decreasing the hypothalamic-pituitaryadrenal axis activity [18] and stabilising but not decreasing the inflammatory cytokine interleukin (IL)-6 [19]. Increased nightly usage of CPAP or a dose response is associated with improved neurocognitive function and better mood [20][21][22].…”
Section: Treatment With Cpapmentioning
confidence: 99%